Social Responsibility and Sustainable Development: the Changing Mission of the Higher School - M. A. Izmailova (Модернизация, инновация, развитие, 2022)
Purpose: of the article is to study the basic principles of higher education and their impact on the formation of a socially active position of universities and their involvement in achieving sustainable development goals on the scale of global humanity.Methods: is based on the application of systemic and institutional approaches to the study of the role of higher education in solving the problems of society, as well as a group of methods of scientifc cognition: dialectical and retrospective, induction and deduction, comparative analysis, the method of rating assessment and others.Results: the essence of the fundamental principles of higher education – academic freedom and academic responsibility, which form the value basis of classical education in its historical period of development, is revealed. In modern conditions, these principles are increasingly reﬂected in the activities of universities related to their key role in solving economic, social and environmental problems. More and more often universities declare their social responsibility and prove it by the example of their decisions in the conditions of social crisis. The COVID-19 pandemic isconsidered one of the crisis situations, and the measures taken by the university leadership to support the teaching staﬀ and its student audience are a kind of indicator of social responsibility. The range of tasks in which the higher school is involved is quite wide. It covers problems of a global nature, one of which is the search for ways of sustainable development of mankind: universities take responsibility for achieving the selected Sustainable Development Goals and report to society for the eﬀectiveness of this area of their activities.Conclusions and Relevance: the implementation by universities of socially responsible behavior towards their internal stakeholders (teachers, students, employees), integration into solving vital problems of society, as well as involvement in achieving Sustainable Development Goals clearly demonstrate the transformation of their mission. Universities enter into an active dialogue with society to solve problems at diﬀerent levels of economic systems, making eﬀorts to combine the spheres of knowledge production, scientifc research expected by society, the transformation of knowledge and scientifc results into practice through the initiation of new directions and activities, technological transformation of the scientifc and educational space, diversifcation of channels of interaction with society